AN ASSESSMENT OF THE VOCATIONAL INTEREST OF STUDENTS IN THE POST-PRIMARY EDUCATION SYSTEM OF ENUGU STATE, NIGERIA - Ene, Emmanuel (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Vocational interest describes the degree to which individuals prefer specific career paths or skilled behavior, which may be typical for various positions. Numerous authors have underscored the patterns and prospects of vocational interest in Nigeria. However, data regarding the dimensions of vocational interest is lacking. The present study assessed the vocational interest of secondary school students relative to the six dimensions. Two hundred and sixty-seven (n=267) post-primary school students were randomly pooled from different public and private secondary schools in Enugu state for the study. A descriptive method was adopted in the study. The percentage scores of the data revealed a higher interest in artistic (22.8%), social (25.8%), enterprising (21.3%), and lower interest in realistic (6%), investigative (7.9%), convention (16.1%). The study concludes that vocational interest in the scientific and skilled workforce is decreasing in contemporary society. The result has implications for developing science and technology-based education in Nigeria.